Looking for answers? Westonci.ca is your go-to Q&A platform, offering quick, trustworthy responses from a community of experts. Experience the convenience of finding accurate answers to your questions from knowledgeable professionals on our platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.

Remove all grouping symbols and combine like terms,
a - { a - [ a- (2a - b) + 3a ]}


Sagot :

[tex]a -\{ a - [ a- (2a - b) + 3a ]\}=\\ a -\{ a - [ a- 2a + b + 3a ]\}=\\ a -\{ a - [ 2a+b ]\}=\\ a -\{ a - 2a - b \}=\\ a -\{ - a- b \}=\\ a+a+b=\\ 2a+b[/tex]
a - { a - [ a- (2a - b) + 3a ]}
= a - {a - (a - 2a + b + 3a)}
= a - {a - (2a + b)}
= a - (a - 2a -b )
= a - (-a - b)
= a + a + b
= 2a + b